PENGGUNAAN ANGGARAN DAN PERTANGtGUNGJAWABAN DALAM RANGKA REVITALISASI PASAR ANYAR OLEH PERUSAHAAN DAERAH PASAR KOTA TANGERANG: The Use of Budget and Accountability in he Context of the Revitalization of the Anyar Market by the Local Market Company of Tangerang City - Dimas Fazar Lazuardy; Tri Sulistyowati (AMICUS CURIAE, 2025)
Market Revitalization is an effort to transform and make updates that can be carried out in traditional markets, old markets that have experienced a decline in attractiveness or infrastructure delays. The author intends to conduct additional research regarding the issue of whether the implementation of the revitalization of Pasar Anyar by the Tangerang City Market Regional Company is in accordance with Regional Regulation Number 1 of 2022. The author also aims to examine the accountability steps taken regarding this utilization. budget for the revitalization of Pasar Anyar by the Tangerang City Market Regional Company. This research is normative legal research that uses a descriptive analytical approach. This research uses secondary data and uses qualitative analysis to draw findings based on deductive reasoning. The conclusion of this research is that the revitalization of Pasar Anyar, Tangerang City, will be carried out from 6 October 2023 to 6 October 2024, for the reason that Pasar Anyar, Tangerang City has inappropriate market conditions in terms of buildings, premises and inadequate parking space, which causing a decrease in people's interest in shopping at Pasar Anyar, so that the economy at Pasar Anyar declines. The revitalization of Pasar Anyar Tangerang City is in accordance with Regional Regulation Number 1 of 2022.